Hadith #4719 - Sunan Abi Dawud - Abu Hurairah; Harun bin al-Ma'ruf هارون بن معروف المروزي الخزاز الضرير; Hisham bin 'Urwa هشام بن عروة; Sufyan bin 'Uyaynah سفيان بن عيينة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The devil flows in a man like his blood.
Grade: Sahih